Miniaturization of Circularly Polarized Patch Antenna for RFID Reader Applications - Mekki, K.; Necibi, O.; Boussetta, C.; Gharsallah, A. (Engineering, Technology & Applied Science Research, 2020)
This paper presents a Circularly Polarized Microstrip Patch Antenna (CPMPA) miniaturization with parasitic elements, suitable for UHF RFID systems. The antenna consists of a half E-shaped patch with cuts. A truncated corner patch can generate an additional Circular Polarization (CP) radiation mode and further enhance the axial ratio. Two symmetric cross shaped slots along the horizontal axis of the CPMPA have been embedded, and its dimension optimization has been based on parametric analysis. Thanks to this slotted structure and reduced surface area, good CP quality has been obtained with a 25% overall size reduction. The proposed antenna is lightweight, low profile, simple, and easily produced. The structure’s simulation is made using CST Studio Suite 2014 to compute return loss (S11), gain, and the axial ratio of the antenna while the overall miniaturized antenna’s volume is 77mm×58mm×1.6mm operating at 915MHz.